Coral cover assessment of five marine protected areas in Davao Oriental for reef conservation and management - Rapiz, France Guillian B. (2014)
Marine protected areas (MPAs) are being established in coral reefs with the goal of protecting and conserving these habitats and the resource therein. The Integrated Coastal Resource Management Project (ICRMP) aims to help Davao Oriental realize this by providing the necessary support to coastal communities for them to establish and manage their MPAs. The objective of this study is to determine the status of coral reefs in five of the ICRMP-assisted MPAs in Davao Oriental to obtain baseline data needed to inform their management. The five MPAs are located in the barangays of Luban, Lanca and Lawigan in the City of Mati; Barangay San Ignacio in Manay; and Barangay Jovellar in Tarragona. The Line Intercept Transect (LIT) method was used in the assessment of benthic life forms. Coral cover inside the MPAs of Barangay Luban and Lawigan in Mati City and Barangay San Ignacio in Manay all fall within the fair category whereas the coral cover of the MPAs in Barangay Lanca, Mati City and Barangay Jovellar, Tarragona are poor. Meanwhile, coral covers outside of the MPAs in this study are all poor except for Barangay Luban, which has a fair coral cover. Among the MPAs, Barangay Lawigan has the highest live hard coral cover while Barangay Jovellar has the lowest. Of the sites assessed outside of the MPAs, Barangay Luban has the highest coral cover while Barangay San Ignacio has the lowest. The results of the assessment in this study will be used as baseline data for future monitoring to determine whether protection has resulted to better coral cover inside the MPAs.
Keywords: Marine Protected Areas; Integrated Coastal Resource Management Project; Coral reef conservation; Mindanao studies